Chronicles of our time - Beteille, Andre (New Delhi ; New York, NY : Penguin Books, 2000)
Collection of articles, most on contemporary social issues prevailing in India.
"This collection brings together the articles that I have published in the editorial pages of the Times of India since 1968." -- Introduction.
Keywords: Social problems -- India; Social justice -- India; India -- Social conditions